Hervada, J. (1981, 2001). Introducción crítica al derecho natural. Pamplona: EUNSA. - Esteban Javier Mosquera Cabrera (Ius Humani. Jornal do direito, 2010)
This review provides a comparison between the different editions of the famous work of Hervada, discussed here. The outcome of this analysis arise five new hermeneutical rules that analyze how to interpret positive law or agreement that eventually undermine the natural law. It is also evident that the principles proposed by Hervada are a good basis for general legal hermeneutics.